Palladium-catalyzed carboxylative cyclization of propargylic amines with aryl iodides, CO2 and CO under ambient pressure. Issue 43 (9th May 2022) - Cai, Shuai-Fang; Qiu, Li-Qi; Huang, Wen-Bin; Li, Hong-Ru; He, Liang-Nian
Abstract : The palladium-catalyzed four-component carboxylative cyclization of propargylic amines, aryl iodides, CO2 and CO was developed, which has broad substrate scope and application prospects. Abstract : A palladium-catalyzed four-component carboxylative cyclization comprising propargylic amines, aryl iodides, CO2 and CO was developed. By selecting Et3 N and 1, 5, 7-triazabicyclo[4.4.0]dec-5-ene (TBD) as the base, respectively, both terminal and internal propargylic amines proceeded well facilitated by Pd(PPh3 )2 Cl2, affording the functionalized 2-oxazolones in moderate yields. This protocol enlarges the product diversity based on CO2 conversion and simultaneously provides a cooperative transformation route for both CO2 and CO.